Assessing the Impacts of Tourism Climate Index and Holiday Climate Index on Tourism Demand in Malaysia - Jong, Meng Chang; Puah, Chin Hong; Mohammad Affendy, Arip (Asia Business Research Corporation Limited, 2023)
This study aims to investigate the impacts of climate change on tourism demand in Malaysia. To date, this is the first study to employ the tourism climate index (TCI) and the holiday climate index (HCI) to examine the linkage between climate variables and tourism demand in Malaysia. Both the TCI and the HCI were constructed by integrating several climatic variables – temperature, humidity, precipitation, cloud cover, duration of sunshine, and wind speed into a single numerical index. The climate indexes were theoretically based on the biometeorological literature to reflect human thermal comfort. This paper utilized the effective temperature to measure human thermal comfort based on the ASHRAE-55 standard and employed monthly data from 2010 through 2020. The weather data were gathered from The Weather Online. Meanwhile, the number of international tourist arrivals to Malaysia was collected from the Ministry of Tourism Malaysia. The empirical outcomes of this study show that both the TCI and the HCI illustrated similar trends with the tourist visitation pattern in Malaysia. These results indicate that the climatic conditions potentially affect demand in Malaysia’s tourism industry. Therefore, both the TCI and HCI provide valuable insights to the Malaysian government and key industry players to design tourism policies and products. Lastly, this study also contributes to the literature related to tourism studies.